Fragmentary bodies or fragmentary perceptions? Mortuary practices of early mesolithic communities in South-western Iberia (c. 11,200–8500 cal BP) - Araújo, Ana Cristina (2020)
Death and attitudes towards death have been always a major concern in Archaeology. This paper deals with the theme in Early Mesolithic societies from Southwest Iberia, presenting the most parsimonious hypothesis about the nature and quality of the human component in the archaeological record. Death and the dead appear extremely fragmentary and disconnected within the sites and the territory, following the apparent pattern observed for the Final Upper Palaeolithic but in clear contrast with the one observed for the Late Mesolithic. From this moment on, the dead became the most featuring trait of the latest hunter-gatherers communities from SW Iberia. We argue that these mortuary differences reveal distinctive worldviews, attitudes and lifestyles of these communities as well as in their interaction with the territory. The Early Mesolithic population from SW Iberia was extremely mobile, organised in small family units, and mortuary behaviour seemed to mirror this same pattern, as if fragmentary death was linked to the lack of territoriality reflected in the archaeological record.